INCREASED EXPRESSION OF PHOSPHATE TRANSPORTER OSPT2, OSPT6 AND A NOVEL GENE NRR NOT ENHANCES THE P-UPTAKE AND ACQUISITION IN RICE (ORYZA SATIVA L.) IN P-STRESS CONDITION - ARIJIT MUKHERJEE; RUPSANATAN MANDAL; ROSHAN RAMESH RAO YELNE; NIRMAL MANDAL (The Bioscan, 2014)
Phosphorus (P) is one of the most important macronutrients in the plant lifecycle. Lack of phosphate (inorganic phosphate, Pi) inhibits plant growth. Here, we report on the expression patterns, and the field validation of two members of this family OsPT2 and OsPT6 along with a novel gene NRR, responds to macronutrient deûciency and regulates root growth. The study showed that the expression of OsPT2, OsPT2 and NRR are much higher in Satabdi, a P-deficient non-tolerant variery, whereas expression is low in P-deficient tolerant genotype, Gobindobhog in P-srtess condition. Thus, OsPT2 , OsPT6 and NRR alleles of Gobindabhog were suitable for introgression into non-tolerant cultivars.